Ekopedagogik : Seperti Apakah Konten yang Tepat Dalam Mengajarkan Anak Tentang Peduli Lingkungan Hidup di Era Globalisasi - Eka Sapta Wati; Aan Listiana (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This research was conducted with the aim of finding out what eco-pedagogical content that educators can use in teaching environmental care values to early childhood. The method used is a systematic review by collecting relevant literature related to ecopedagogy in early childhood. The results of this study indicate that there are some ecopedagogic content that can be used as learning materials for early childhood, including through green school, digital media, creative dance, out bound, field trips and storytelling methods. All of this content is very effectively applied to early childhood, because the learning process is carried out to be more meaningful for children and in accordance with the characteristics of children in this era of globalization